Inflasi dan Jumlah Uang Beredar: Pengaruhnya terhadap Nilai Tukar Mata Uang Rupiah Per Dolar Amerika - Dzaky Ahmad Raihan; Muhammad Fauzi; Muhammad Rifki; Fitria Rahmah (PPJP ULM, 2024)
The swapping scale, especially the Rupiah's worth comparable to the US dollar, is critical to the Indonesian economy. The import and product of these wares and not set in stone by the money rate. Since the execution of this framework, unfamiliar monetary forms, especially the US Dollar, fundamentally affect the Rupiah conversion scale. The motivation behind this study is to find out what the cash supply and expansion mean for trade rates. Inflation and the quantity of money in circulation are numerous macroeconomic factors that influence exchange rates. A logical examination procedure is utilized related to quantitative exploration philosophy. In this study, secondary data sources were used. Information that has already been gathered and analyzed by another party and is available in the form of publications is referred to as secondary data. The Rupiah exchange rate is impacted simultaneously by inflation and the money supply. Given their interdependence, a wide range of macroeconomic factors, including inflation rate and money supply, can impact the rupiah's value.